Sexual harassment in Dentistry: prevalence in dental school (Journal of Applied Oral Science, 2010)
OBJECTIVE: Sexual harassment is unlawful in all work and educational environments in most nations of the world. The goals of this study were to describe the sexual harassment prevalence and to evaluate the experiences and attitudes of undergraduate students in one dental school in Brazil. MATERIAL AND METHODS: An 18-item questionnaire was administered to 254 dental students with a completion rate of 82% (208). Students were requested to respond to questions about their background and academic level in dental school, their personal experiences with sexual harassment and their observation of someone else being sexually harassed. Bivariate statistical analyses were performed. RESULTS: Fifteen percent of the students reported being sexually harassed by a patient, by a relative of a patient or by a professor. Male students had 3 times higher probability of being sexually harassed than female student [OR=2.910 (1.113-7.611)]. Additionally, 25.4% of the students reported witnessing sexual harassment at the school environment. The majority of students did not feel professionally prepared to respond to unwanted sexual behaviors. CONCLUSION: These findings demonstrate that sexual harassment can occur in a dental school setting. There is a need for ongoing sexual harassment education programs for students and university staff. Increased knowledge of sexual harassment during graduation can better prepare dental professionals to respond to sexual harassment during their practice.